PROBLEMS OF CORRUPTION IN PUBLIC ADMINISTRATION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Corruption in the public administration system has a negative impact on the economy of Kyrgyzstan, leads to an inadequate perception of the economic, political and social reforms being carried out in the republic. The negative consequences of corruption lead to a significant decrease in the level of controllability of state authorities, primarily in the economic sphere, resulting in a decrease in tax revenues, budget instability and inefficient use of budget funds, especially in the distribution of government orders and purchases. These circumstances make the fight against corruption in Kyrgyzstan one of the most important tasks for today and for the future.
Keywords: сorruption, state, politics, power, society, system, body, institution, law, budget.